The Impact Of Business Development Assistance Programs Pengembangan Usaha Mina Pedesaan (Pump) Fishing Culture In Kelurahan Lembah Sari Kecamatan Rumbai Pesisir Pekanbaru City Riau Province - Ilham Drizal; Kusai '; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
To determine the impact of business development assistance programs Pengembangan Usaha Mina Pedesaan (PUMP) aquaculture in Kelurahan Lembah Sari Kecamatan Rumbai Pesisir Pekanbaru Riau. We propose the problem of, how the production and in come of fish farmers group members before and after receiving assistance program PUMP Aquaculture. Order to answer the sequestions, this study used asurvey method of obtaining information with personally and directly interviewed various groups or persons.The results showed that with the help of the program PUMP Fishing Culture, the increasing income of fish farmers also have an impact one forts to meet the needs of each member of the group farming house holds are getting better.Keywords: Mina, Aquaculture, fish culture, assistance of PUMP